Effect of Digital Devices and Parental Regulations on Adolescents' Achievement Motivation: A Quantitative Study - Yadav, Monika; Dube, Shubha (Indian Journal of Extension Education, 2025)
The increasing reliance on digital devices presents both benefits and challenges, particularly during adolescent years. The present study was conducted from January to December 2024. A sample of 300 adolescents aged 14-16 years was selected. Quantitative research design, self-structured close-ended questionnaires were administered through surveys. The study aimed to investigate the impact of digital devices and parental rules on the achievement motivation of adolescents. Participants reported that the use of digital devices for educational purposes and the time spent on these devices for school assignments significantly influenced their motivation. The findings indicated that distractions and lack of concentration in the classroom, attributed to digital devices, adversely affected the participants' achievement motivation. Results also demonstrated that digital devices offer opportunities for personality development, which in turn influences achievement motivation. Parental regulations on screen time played a crucial role in shaping adolescent motivation, emphasising the importance of structured digital habits. The findings can assist teachers, educational institutions, policymakers, and counsellors in promoting mindful digital habits. Encouraging balanced screen exposure and reinforcing achievement motivation can contribute to healthier academic and psychological development among adolescents.